2008
DOI: 10.1897/08-123.1
|View full text |Cite
|
Sign up to set email alerts
|

Apparent tolerance of turkey vultures (Cathartes aura) to the non‐steroidal anti‐inflammatory drug diclofenac

Abstract: The nonsteroidal anti-inflammatory drug diclofenac is extremely toxic to Old World Gyps vultures (median lethal dose -0.1-0.2 mg/kg), evoking visceral gout, renal necrosis, and mortality within a few days of exposure. Unintentional secondary poisoning of vultures that fed upon carcasses of diclofenac-treated livestock decimated populations in the Indian subcontinent. Because of the widespread use of diclofenac and other cyclooxygenase-2 inhibiting drugs, a toxicological study was undertaken in turkey vultures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 24 publications
(46 reference statements)
1
51
0
Order By: Relevance
“…In addition, these vultures always demonstrated massive increases in serum uric acid concentrations with concurrent visceral gout evident on necropsy. Our findings were, however, very similar to those previously reported for Turkey Vultures (Rattner et al, 2008), suggesting that toxicity is not linked to consumption of carrion (and consequential to high uric acid generation) but to other biochemical factors.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, these vultures always demonstrated massive increases in serum uric acid concentrations with concurrent visceral gout evident on necropsy. Our findings were, however, very similar to those previously reported for Turkey Vultures (Rattner et al, 2008), suggesting that toxicity is not linked to consumption of carrion (and consequential to high uric acid generation) but to other biochemical factors.…”
Section: Discussionsupporting
confidence: 91%
“…The pharmacokinetic parameters (in comparison to other avian species) demonstrated a clear relationship between half-life and death/toxicity (Table 3; Swan et al, 2006b;Naidoo et al, 2007Naidoo et al, , 2009Rattner et al, 2008). In all cases where plasma concentration data were available, birds tended to die when half-life elimination was above 12 hr.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Further, controlled toxicity studies have now shown that diclofenac is also toxic to three other Gyps vulture species (G. africanus, G. coprotheres and G. fulvus) as well as the domestic chicken (Gallus gallus), although at a higher dose for the latter (Swan et al 2006b;Naidoo et al 2007. At the same time, it has been clearly shown to be safe at very high doses in Turkey vultures (Cathartes aura) (Rattner et al 2008) and in House crow (Corvus albus; unpublished work). Hence, very signiWcant diVerences in toxicity between diVerent bird species clearly exist.…”
Section: Introductionmentioning
confidence: 99%